Different doses of micafungin for prophylaxis of invasive fungal diseases in hemato-oncological high-risk patients: a web-based non-interventional trial in four large university hospitals in Germany - Heimann, S. M.; Vehreschild, M. J. G. T.; Meintker, Lisa; Heinz, W.; Schroeder, T.; Von Bergwelt-Baildon, M.; Cornely, O. A.; Vehreschild, J. J. (Transplant Infectious Disease, 2014)
Treatment indications of new antifungals in clinical practice often deviate from the strict criteria used in controlled clinical trials. Under routine clinical conditions, beneficial and adverse effects, not previously described in clinical trials may be observed. The aim of this study was to describe customary prescription and treatment strategies of micafungin (MCFG).A registry was set up on www.ClinicalSurveys.net and physicians were invited to provide retrospective information on cases they had treated with MCFG. Documentation comprised demographic information, underlying disease, effectiveness, safety, and tolerability of MCFG.A total of 125 episodes of patients hospitalized between September 2009 and February 2012 were documented, of which 7 had to be excluded because of incomplete documentation. The most common risk factors of patients were hematological malignancy (n = 116, 98.3%) and antibiotic treatment >3 days (n = 115, 97.5%). MCFG was administered as prophylaxis in 106 (89.9%) patients. Median duration of MCFG application as prophylaxis was 21 days (range: 3-78); 53 of the patients (50%) received a dose of 50 mg, while the other 53 (50%) received 100 mg/day. For the different doses, prophylactic outcome was rated as success in 42 (79.2%) vs. 52 (98.1%; P = 0.004) patients. Fifty-five patients (51.9%) were treated with posaconazole before initiation of MCFG. Four patients (7.5%) developed a proven invasive fungal disease (IFD) while being treated with 50 mg MCFG, compared to no patient treated with 100 mg (P = 0.118). At the end of MCFG prophylaxis, 24 (22.6%) patients were switched to fluconazole and 64 (60.3%) patients to posaconazole.Our study shows clinical effectiveness of MCFG prophylaxis with low rates of breakthrough fungal infections. In most cases, MCFG was part of a multi-modal antifungal prophylactic strategy. Investigators reported fewer proven IFDs in patients receiving therapeutic doses of MCFG as prophylaxis.
EVALuna2:25712